1990
DOI: 10.1073/pnas.87.14.5258
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct forms of active transcription factor CREB (cAMP response element binding protein).

Abstract: Mammalian cells express two distinct forms of transcription factor CREB (cAMP response element binding protein) that are apparently the products of alternative splicing of the CREB gene transcript. The two proteins differ by a 14-amino acid serine-rich insertion present in one of the CREB isoforms. We show that both CREB isoforms are expressed in many cell types and mammalian species. Both encode proteins that bind specifically to a cAMP response element in vitro. As expected for proteins of this class, the CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 26 publications
2
56
0
Order By: Relevance
“…Yamamoto et al (35) found that CREB341 is more active than CREB327 in stimulating transcription from the somatostatin gene CRE. However, in two other studies the presence of the cc peptide did not result in increased CREB activity (34,36). Therefore, the functional significance of the cc peptide is still unclear.…”
Section: Regulation Of Gene Transcription By Protein Kinase A-specifimentioning
confidence: 99%
“…Yamamoto et al (35) found that CREB341 is more active than CREB327 in stimulating transcription from the somatostatin gene CRE. However, in two other studies the presence of the cc peptide did not result in increased CREB activity (34,36). Therefore, the functional significance of the cc peptide is still unclear.…”
Section: Regulation Of Gene Transcription By Protein Kinase A-specifimentioning
confidence: 99%
“…The membrane was detected with anti-phosphorylated CREB (Upstate Biotechnology) or anti-CREB (25) using ECL reagents (Amersham). The doublet of CREB corresponding to CREB341 and CREB327 was previously reported (70). pCREB, CREB phosphorylated at Ser 133 .…”
Section: Synergistic Effect Of Erk P38 Mapk and Ca 2ϩ On Creb Transmentioning
confidence: 99%
“…In addition, we also tested a modified form of NF-KB p65, NF-KB p65mLZ, containing a point mutation in a recently VOL. 13,1993 described leucine zipper-like structure (73). For comparison of the effects of rat C/EBPP on KB enhancer-dependent gene expression, the amounts of transfected expression vectors for NF-KB proteins were adjusted to obtain similar levels of induced CAT activity.…”
mentioning
confidence: 99%
“…The mouse c-Jun, human c-Fos, and human CREB pCMV4T expression vectors contain full-length coding sequences of the corresponding T7 polymerase-driven vectors (13,69,70) cloned downstream of the CMV immediate-early-region promoter. The wild-type Myb expression vector (pRmb3SVneo) and the corresponding frameshift control pJTmyb-fs have been described elsewhere (25).…”
mentioning
confidence: 99%